Thermoelectric properties of co-doped (Bi0.98In0.02)2Te2.7Se0.3 /reduced graphene oxide composites prepared by solid-state reaction. (January 2022) - Hegde, Ganesh Shridhar; Parol, Vinay; Rao, Ashok; Prabhu, A.N.; Levinsky, Joshua J.B.; Blake, Graeme R.
Highlights: A reduced graphene oxide of (Bi0.98 In0.02 )2 Te2.7 Se0.3 prepared using single step solid state reaction is reported, and thermoelectric performance is investigated in the temperature range 10 - 325 K. From the powder X-ray diffraction study, it is observed that composites adopt a rhombohedral structure with space group R 3 ¯ m . The thermal conductivity and electrical resistivity of (Bi0.98 In0.02 )2 Te2.7 Se0.3 /0.02 wt% reduced graphene oxide composite are found to decrease by 1.6 and 10 times respectively in comparison with that of (Bi0.98 In0.02 )2 Te2.7 Se0.3 . The power factor is enhanced by 7 times for (Bi0.98 In0.02 )2 Te2.7 Se0.3 /0.01 wt% rGO compared to that of (Bi0.98 In0.02 )2 Te2.7 Se0.3 . Abstract: The thermoelectric properties of co-doped (Bi0.98 In0.02 )2 Te2.7 Se0.3 /reduced graphene oxide composites between 10 - 325 K are presented. X-ray diffraction confirms that the composites adopt a rhombohedral structure with space group R 3 ¯ m . Field emission scanning electron microscopy reveals an interface structure of reduced graphene oxide (rGO). N-type conducting behaviour is observed for all the samples, as ascertained by Hall effect and Seebeck coefficient measurements, with a carrier concentration of 10 25 /m 3 . The thermal conductivity and electrical resistivity of (Bi0.98 In0.02 )2 Te2.7 Se0.3 /0.02 wt% reduced graphene oxide composite is found to decrease by 1.6 and 10 times respectively in comparison with that of (Bi0.98 In0.02 )2 Te2.7 Se0.3 . The power factor is enhanced by 7 times for (Bi0.98 In0.02 )2 Te2.7 Se0.3 /0.01 wt% rGO compared to that of (Bi0.98 In0.02 )2 Te2.7 Se0.3 . Graphical abstract: Image, graphical abstract